A pan‐genome and chromosome‐length reference genome of narrow‐leafed lupin (Lupinus angustifolius) reveals genomic diversity and insights into key industry and biological traits. (11th August 2022) - Garg, Gagan; Kamphuis, Lars G.; Bayer, Philipp E.; Kaur, Parwinder; Dudchenko, Olga; Taylor, Candy M.; Frick, Karen M.; Foley, Rhonda C.; Gao, Ling‐Ling; Aiden, Erez Lieberman; Edwards, David; Singh, Karam B.
SUMMARY: Narrow‐leafed lupin (NLL; Lupinus angustifolius ) is a key rotational crop for sustainable farming systems, whose grain is high in protein content. It is a gluten‐free, non‐genetically modified, alternative protein source to soybean ( Glycine max ) and as such has gained interest as a human food ingredient. Here, we present a chromosome‐length reference genome for the species and a pan‐genome assembly comprising 55 NLL lines, including Australian and European cultivars, breeding lines and wild accessions. We present the core and variable genes for the species and report on the absence of essential mycorrhizal associated genes. The genome and pan‐genomes of NLL and its close relative white lupin ( Lupinus albus ) are compared. Furthermore, we provide additional evidence supporting LaRAP2‐7 as the key alkaloid regulatory gene for NLL and demonstrate the NLL genome is underrepresented in classical NLR disease resistance genes compared to other sequenced legume species. The NLL genomic resources generated here coupled with previously generated RNA sequencing datasets provide new opportunities to fast‐track lupin crop improvement. Significance Statement: This manuscript presents a chromosome‐length reference assembly for narrow‐leafed lupin ( Lupinus angustifolius ) and a pan‐genome and using this resource identifies a candidate gene for the regulation of alkaloid biosynthesis. In addition, a low number of classical disease resistance genes are identified in the genome and key genes associated with mycorrhizal associations are absent in the assemblies.